IS-RPB-intensified resource utilization of coal fly ash coupled with multidimensional techno-economic and life cycle assessment - Zhiguo Yuan; Zhong Guo; Chunge Dang; Shuli Zhang; Youzhi Liu; Ruichen Wang (Process Safety and Environmental Protection, 2026)

Physics-Informed Deep-Learning Prediction of Tropical Cyclone Wind Size in the Western North Pacific - Ruichen Guo; Jing Xu; Chi Yang; Mingzhu Zhou (Journal of Meteorological Research, 2026)

Discovering VEGFR-targeting constituents from Chloranthus holostegius guided by affinity screening - Wenhui Liu; Haojing Jiang; Xinxing Li; Ruichen Guo; Jing Xu; Yuanqiang Guo (Phytochemistry, 2025)

Oil pollution risks on coastlines in the Eastern China Seas - Ruichen Cao; Junting Guo; Zengrui Rong; Haibo Chen; Xianqing Lv (Environmental Pollution, 2025)

Techno-economic-environmental analysis based on life cycle carbon accounting and pollutants audit for cleaner production of electrolytic manganese - Ruichen Wang; Shuli Zhang; Yajing Guo; Jingyang Liu; Feilong Zhang; Chunge Dang (Process Safety and Environmental Protection, 2024)

Temporal and spatial variations in squid jigging catch efficiency in the Oyashio Extension region - Zixuan Niu; Zhaohui Chen; Wei Yu; Haihong Guo; Ruichen Zhu; Xiaoyi Zhang (Fisheries Oceanography, 2024)
The abundance of fishery resources significantly impacts the ratio of fishing effort to harvest. However, traditional statistics of fishery catches or commonly used catch per unit effort (CPUE) metrics cannot accurately capture the complexity of resource abundance in the ocean. To address this issue, we propose here a novel approach that integrates the actual fishery catch from vessel logs with fishing duration obtained through automatic identification system (AIS) positioning. This combined analysis eliminates confounding factors and introduces a novel metric called “catch efficiency (CE)” to evaluate fishing operations more accurately, thereby reflecting resource abundance in a more reasonable way. In this study, we focus on the CE of squid in the Oyashio Extension region in the Northwestern Pacific. Our analysis reveals significant temporal and spatial variations of CE, manifesting in both intensity and distribution patterns. Moreover, our findings establish a close relationship between CE and background water mass distribution, chlorophyll‐a concentration, and micronekton biomass. This implies that the resource abundance of squid can be inferred by considering the varying environmental factors within the fishing area.

Regional to global assessments of ocean transparency dynamics from 1997 to 2019 - Junting Guo; Zihan Zhao; Ruichen Cao; Xianqing Lv (Progress in Oceanography, 2023)

Secotrijugins A−D, four highly oxidized and rearranged limonoids from Trichilia sinensis and their anti-inflammatory activity - Honghong Xing; Ziteng Song; Ruichen Guo; Feng Liu; Lijun An; Yuanqiang Guo; Ping Hu (Phytochemistry, 2023)